Narratives of Slow Violence Fear by Greek-speaking Pregnant Women during the COVID-19 Period - Vasiliki Saini (Randwick International of Social Science Journal, 2023)
During the COVID-19 pandemic pregnant women had to cope with the unknown and unprecedented challenges the coronavirus health crisis created. The Greek state and the biomedical discourse classified pregnant women as vulnerable due to the increased risk of severe illness and mortality rate of pregnant women infected by the coronavirus, depriving them of any kind of agency. However, the fear of slow violence of potential COVID-19 infection to the fetus’s health and the health of pregnant women led them, and particularly, the participants in this research, to act agentively as self risk-managers and to proceed to the adoption of several measures in order to alleviate this fear and to safeguard their own and their fetus’s health. These measures consisted of self-regulated preventive measures, mitigation strategies, and the COVID-19 vaccine uptake or refusal. These findings constituted the voice of the interviewees and their experience of being pregnant during the COVID-19 pandemic. They were the outcome of the conduct of eighteen online formal semi-structured in-depth online interviews and netnography. The research lasted three months, from 10 February 2022 to 10 May 2022, and was conducted in framework of the thesis: The experience of pregnancy in the COVID-19 period in Greece at the Master Course: Cultural Anthropology-Sustainable Citizenship of Utrecht University.